Sympathetic Influence on Capsaicin-Evoked Enhancement of Dorsal Root Reflexes in Rats - Wang, Jing; Ren, Yong; Zou, Xiaoju; Fang, Li; Willis, William D; Lin, Qing (Journal of neurophysiology, 2004)
1 Department of Anatomy and Neuroscience, 2 Division of Neurosurgery in Department of Surgery, The University of Texas Medical Branch, Galveston, Texas 77555-1069 Submitted 12 February 2004; accepted in final form 21 May 2004 A series of experiments by our group suggest that the initiation and development of neurogenic inflammation in rats are mainly mediated by dorsal root reflexes (DRRs), which are conducted centrifugally from the spinal dorsal horn in primary afferent nocieptors. In this study, DRRs were recorded in anesthetized rats from single afferent fibers in the proximal ends of cut dorsal root filaments at the L 4 L 6 level and tested for responses to intradermal injection of capsaicin. Sympathectomy combined with pharmacological manipulations were employed to determine if the capsaicin-evoked enhancement of DRRs was subject to sympathetic modulation. DRRs could be recorded from both myelinated (A and A ) and unmyelinated (C) afferent fibers. After capsaicin was injected intradermally into the plantar foot, a significant enhancement of DRRs was seen in C- and A -fibers but not in A -fibers. This enhancement of DRRs evoked by capsaicin injection was almost completely prevented by sympathectomy. However, if peripheral 1 -adrenoceptors were activated by intra-arterial injection of phenylephrine, the enhancement of DRRs evoked by capsaicin could be restored, whereas no such restoration was seen following pretreatment with an 2 -adrenoceptor agonist, UK14,304. Under sympathetically intact conditions, the enhanced DRRs following capsaicin injection could be blocked by administration of terazosin, an 1 -adrenoceptor antagonist, but not by administration of yohimbine, an 2 -adrenoceptor antagonist. These results provide further evidence that the DRR-mediated neurogenic inflammation depends in part on intact sympathetic efferents acting on peripheral 1 -adrenoceptors, which augment the sensitization of primary afferent nociceptors induced by capsaicin injection, helping trigger DRRs that produce vasodilation. Address for reprint requests and other correspondence: Q. Lin, Dept. of Anatomy and Neuroscience, The Univ. of Texas Medical Branch, 301 University Blvd., Galveston, TX 77555-1069 (E-mail: qilinatutmb.edu ).